Histological study of human fetuses vertebral column ossification. - Kabak, S. L.; Zatochnaya, V. V.; Melnichenko, Y. M.; Mohammadi, T. M. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. The study of normal embryonic development of the vertebral column is important for understanding the pathogenesis of congenital anomalies of the axial skeleton. Objective. To study the histodifferentiation of cartilage and bone tissue in the vertebral centra and neural arches of particular parts of the vertebral column in human embryos of the first half of fetal development. Methods. Whole-mount skeletal preparations, stained with alcian blue and alizarin red, as well as serial histological sections from the embryological collections of the Belarusian State Medical University and from the Carnegie collection (3D Atlas of Human Embryology project, https://www.ehd.org/virtual-human-embryo/) using hematoxylin and eosin and Masson’s trichrome staining were studied. A total of 37 human embryos/fetuses from 5 to 20 weeks of age were used. Results. "Primary" centers of ossification were found in the neural arches of the upper cervical and centra of lower thoracic and upper lumbar vertebrae of 9-10-week human embryos. They consist of hypertrophic chondrocytes surrounded by a mineralized matrix. Complete ossification of the cartilaginous anlages of the vertebral bodies begins at 12 week of embryogenesis. The appearance of the osteoid and structural elements of the bone marrow in their centers is preceded by the ingrowth of vascular canаls. In the vertebral neural arches, the formation of bone tissue occurs due to endochondral and perichondral ossification. Three growth zones are formed near the ossification center – one is for the region of the pedicle of the neural arch; the other for the lamina/spinous process; the third – for the base of the transverse process. Conclusion. According to the histological structure, the ossification of the vertebral body is similar to the "secondary" ossification center of long bone, and the ossification center in the neural arch at the microscopic level resembles the diaphyseal ossification center of the long bone. Differences in the timing of appearance and osteogenic pathways of the vertebral centra and neural arches are determined by different sources of their origin.